The role of industrial parks in the economic development of Debrecen - Kozma, Gábor; Molnár, Ernő (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2018)
In recent times, industrial parks have played a very important role in the development of the Hungarian economy, and in the spirit of the above, local governments have also paid special attention to these facilities. The purpose of this paper is to analyse the role of industrial parks in economic development in the case of a specific settlement; the city of Debrecen. The most important research findings are the followings: on the one hand, industrial parks have been an essential element of local economic development documents since the early 1990s; on the other hand, the companies operating in the industrial parks constitute an important base of the city’s economy, a role which is also expected to remain in the future.